AIP limits neurotransmitter release by inhibiting calcium bursts from the ryanodine receptor. Issue 1 (December 2017) - Chen, Bojun; Liu, Ping; Hujber, Edward; Li, Yan; Jorgensen, Erik; Wang, Zhao-Wen
Abstract Pituitary tumors are frequently associated with mutations in theAIP gene and are sometimes associated with hypersecretion of growth hormone. It is unclear whether other factors besides an enlarged pituitary contribute to the hypersecretion. In a genetic screen for suppressors of reduced neurotransmitter release, we identified a mutation inCaenorhabditis elegans AIPR-1 (AIP-related-1), which causes profound increases in evoked and spontaneous neurotransmitter release, a high frequency of spontaneous calcium transients in motor neurons and an enlarged readily releasable pool of vesicles. Calcium bursts and hypersecretion are reversed by mutations in the ryanodine receptor but not in the voltage-gated calcium channel, indicating that these phenotypes are caused by a leaky ryanodine receptor. AIPR-1 is physically associated with the ryanodine receptor at synapses. Finally, the phenotypes inaipr-1 mutants can be rescued by presynaptic expression of mouse AIP, demonstrating that a conserved function of AIP proteins is to inhibit calcium release from ryanodine receptors. In this work the authors show that AIP (aryl hydrocarbon receptor-interacting protein), a gene frequently mutated in association with pituitary tumors, regulates neurotransmitter release by inhibiting calcium release from ryanodine receptors.